PRMT1-mediated methylation of MICU1 determines the UCP2/3 dependency of mitochondrial Ca2+ uptake in immortalized cells - Corina T. Madreiter-Sokolowski; Christiane Klec; Warisara Parichatikanond; Sarah Stryeck; Benjamin Gottschalk; Sergio Pulido; Rene Rost; Emrah Eroglu; Nicole A. Hofmann; Alexander I. Bondarenko; Tobias Madl; Markus Waldeck-Weiermair; et al. (Nature Communications, 2016)
MICU1 is a regulatory subunit of mitochondrial Ca2+ channels that shields mitochondria from Ca2+ overload. Here the authors show that MICU1 methylation by PRMT1 reduces Ca2+ sensitivity, which is normalized by UCP2/3, re-establishing mitochondrial Ca2+uptake activity.